ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRAKTIK INCOME SMOOTHING (Studi Pada Perusahaan Manufaktur Terdaftar di BEI 2009-2012) - Arinta Eka Wahyuni; Yudhanta Sambharakresna; Anita Carolina (JAFFA, 2013)
The objective of this research is to empirically examine firm size, profitability,financial Leverage, institutional ownership, auditor reputation, and dividend payoutfor income smoothing both partially and simultaneously. This study used aquantitative approach, in which of data used is of financial statements 2009-2012period. The samples used were 58 companies with purposive sampling method. Thedata Analysis is using probit regression analysis. The results of this research showed that in partial firm size significantly influenceincome smoothing while profitability, financial Leverage, institutional ownership,auditor reputation, and dividend payout no significant effect on income smoothing.Simultaneously, company size, profitability, Leverage financial, institutionalownership, auditor reputation, and dividend payout influence income smoothing.